FRI0331 Examination of Some Ultrasonographic Parameters of the Heart and Carotid Arteries for Assessment of Cardiovascular Risk in Gout. (9th June 2015) - Gancheva, R.N.; Kundurdjiev, A.; Ivanova, M.; Kundurdzhiev, T.; Rashkov, R.; Kolarov, Z.
Abstract : Background: In the link between gout and cardiovascular (CV) disease many factors are involved: chronic inflammation, renin-angiotensin system and the imbalance between nitric oxide and reactive oxygen species. Often to them factors of the metabolic syndrome are added. Scoring systems have been established for assessment of CV risk. They could not assess all risk factors, as hyperuricemia and gout are not evaluated by them. Objectives: To determine some commonly measured parameters of the heart and morphological changes in the common carotid arteries as a marker of subclinical atherosclerosis. Methods: A total of 169 patients (pts) were divided into four groups: Healthy controls (n=41) in a mean age 55.3±12.9 years, 20 males and 21 females, asymptomatic hyperuricemia (n=41) in a mean age 54.6±15.6 years, 23 males and 18 females, gouty arthritis without tophi (n=49) in a mean age 55.5±11.7 years, 43 males and 6 females and gouty tophi pts (n=38), 37 males and 1 female in a mean age 58.3±11.1 years. All pts underwent a complex multimodal ultrasonography. The following parameters were measured: left ventricular end-diastolic volume (LVEDV), left ventricular end-systolic volume (LVESV), stroke volume (SV), ejection fraction (EF), fraction of shortening (FS), peak systolic mitral annular velocity (Sm), left ventricular mass index (LVMI), intima-media thickness (IMT) and the frequency of atherosclerotic plaques. Ultrasound examinations were performed once by a single investigator unaware with the protocol of the study. Statistical analyses were done by x 2 -test, Kolmogorov-Smirnov, ANOVA, Post-Hoc Tukey and binary logistic regression. Results: Significant difference in IMT (p<0.001), LVMI (p<0.001) and Sm (p<0.001) was found between controls and the three pts' groups. Comparing controls with gouty tophi we observed a significant difference in LVEDV (mean ± SD; 99.88±27.41 vs 124.50±36.19, p=0.007), LVESV (mean ± SD; 28.80±9.73 vs 42.47±19.83, p<0.001), EF (mean ± SD; 71.52±4.35 vs 66.85±6.59, p=0.002), FS (p=0.009) but no significant difference in SV (p=0.398). Gouty tophi compared to asymptomatic hyperuricemia had greater IMT (p=0.001) and LVMI (p=0.002). In gouty tophi we established a moderate correlation between IMT and LVMI (r=0.376, p=0.022) and a strong inverse correlation between FS and LVMI (r= -0.530, p=0.001). By using x 2 -test an association between the examined diseases and the frequency of atherosclerotic plaques was found, (p=0.044). In asymptomatic hyperuricemia 29.3% of pts had plaques, 53.1% in gout without tophi and 52.6% in gouty tophi. Binary logistic regression showed that the increase of IMT with 0.01mm rises the subject's likelihood of having gouty tophi with an OR=1.074 (95% CI 1.027-1.125, p=0.002), while an increase in LVMI by 1.0gr/m 2 rises the risk with an OR=1.052 (95% CI 1.016-1.089, p=0.005). Conclusions: An increase in IMT and LVMI was independently associated with the development of tophi. LVMI and IMT can be easily determined by ultrasound and have proven significance as predictors of CV risk. Tophi are active granulomas leading to chronic inflammation and their appearance defines higher CV risk. Disclosure of Interest: None declared